Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France), attitudes performatives; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Les Presses du réel, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Duke University Press, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Section: x, 219 p. : ill. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles